The Leadership of School Principals in Management Student at SMPI Alhuda Brondong Lamongan - Ahmad Khamsa Fardan; Muhammad Hambal (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
This study is intended to discuss: 1) How leadership head school islamic junior high school al-huda brondong lamongan? 2) How management in junior high school student islamic al-huda brondong lamongan? 3) The extent to which leadership school principals in the junior high school student islamic al-huda brondong lamongan? The kind of research this is qualitative using descriptive analysis. Qualitative Engineering data collection in this research: observation , interview and documentation. While engineering analysis of the research is, data collection data, display data reduction and data conclution. The result of this research concluded: 1) Junior high school principals islam al-huda brondong lamongan has run its role in accordance with its scope. In his leadership school principals have tried to improve school, put out the quality of education and his leadership. 2) A form of implementation student management